Capacity-Strengthening in Research Management: A Case Study of the Advancing Research Management Training Initiative in West Africa - Owoaje, Eme; Adetayo, Adebowale; Kanteh, Dembo (Journal of Research Management and Administration, 2026)
What is new? There is a growing recognition of the need to strengthen research management capacity in West African institutions, yet limited structured training programs exist to address capacity gaps in this field. This study presents original findings from a multi-country initiative aimed at filling that gap. What was the approach? The study employed a pre–post evaluation design using structured surveys administered to participants of three five-day intensive workshops held in Nigeria and Senegal between September and December 2024. The training focused on research support, research strategy, grant writing, budgeting, research communications, integrity, project management, contracts, intellectual property, and gender issues. What is the academic impact? The results revealed significant improvements in participants' self-reported knowledge and competencies across all training areas. The study contributes empirical evidence to the field of Research Management and Administration (RMA), demonstrating the effectiveness of targeted capacity-building interventions in enhancing research support functions in low-resource settings. What is the wider impact? The positive outcomes highlight the potential of structured, context-specific training to build a more competent research management workforce, thereby supporting stronger institutional research environments across West Africa.